C4d Detection in Renal Allograft Biopsies: Immunohistochemistry vs. Immunofluorescence - Santos, A (2013)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2013-02-20T12:53:45Z No. of bitstreams: 1 RPNH 2012 272.pdf: 2322463 bytes, checksum: 743918a7221d817d63e193425458ff5e (MD5)